PENGARUH TINGKAT STRES, GAYA HIDUP DAN KONTROL DIRI TERHADAP KEPUTUSAN PEMBELIAN DARI BRAND KOPI KENANGAN PADA KALANGAN GEN Z - Gita Pundarika Putri Wijaya; William Widjaja (Publika Citra Media, 2026)
This study aims to examine the effects of Stress Level, Lifestyle, and Self-Control on Purchasing Decisions of Kopi Kenangan among Generation Z in Jabodetabek area. A quantitative approach was employed using a survey method with purposive sampling, and the data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that Stress Level has a positive and significant effect on Purchasing Decisions, suggesting that higher stress encourages consumers to make purchases as an emotional coping mechanism. Lifestyle also shows a positive and significant influence, indicating that Kopi Kenangan consumption is closely related to the lifestyle and social activities of Generation Z. Meanwhile, Self-Control has a positive but insignificant effect on purchasing decisions, implying that self-control does not significantly restrain purchasing behavior in this context. These findings contribute to consumer behavior studies and provide practical insights for marketing strategies targeting Generation Z.